Reproductive aging in farm animals: Impacts on fertility and strategies for mitigation: A narrative review - Akhter Rasool; Sachin; Irtiqa Manzoor; Akshata Patil (Asian Pacific Journal of Reproduction)
The livestock sector is a vital component of India's agricultural economy, providing essential support to rural communities and ensuring food security. Efficient reproductive performance is critical to sustaining livestock productivity, yet age-related declines in both male and female fertility pose significant challenges. The current review highlights that male reproductive efficiency is closely tied to semen quality, which deteriorates with age due to oxidative stress, leading to reduced fertilizing capacity and embryonic developmental potential. Similarly, female reproductive longevity is predominantly influenced by ovarian health, which declines with age due to diminished oocyte quality and quantity. This decline is exacerbated by oxidative stress and mitochondrial dysfunction, leading to reproductive senescence and reduced offspring viability. Understanding the mechanisms of reproductive aging and developing strategies to mitigate its effects are crucial for enhancing livestock productivity and sustaining the agrarian economy.